Nucleotide dependent switching in Rho GTPase: conformational heterogeneity and competing molecular interactions - Kumawat, Amit; Chakrabarty, Suman; Kulkarni, Kiran (Scientific Reports, 2017)
Ras superfamily of GTPases regulate myriad cellular processes through a conserved nucleotide (GTP/ GDP) dependent switching mechanism. Unlike Ras family of GTPases, for the Rho GTPases, there is no clear evidence for the existence of "sub-states" such as state 1 & state 2 in the GTP bound form. To explore the nucleotide dependent conformational space of the Switch I loop and also to look for existence of state 1 like conformations in Rho GTPases, atomistic molecular dynamics and metadynamics simulations on RhoA were performed. These studies demonstrate that both the nucleotide-free state and the GDP bound "OFF" state have very similar conformations, whereas the GTP bound "ON" state has unique conformations with signatures of two intermediate states. The conformational free energy landscape for these systems suggests the presence of multiple intermediate states. Interestingly, the energetic penalty of exposing the non-polar residues in the GTP bound form is counter balanced by the favourable hydrogen bonded interactions between the gamma- phosphate group of GTP with the highly conserved Tyr34 and Thr37 residues. These competing molecular interactions lead to a tuneable energy landscape of the Switch I conformation, which can undergo significant changes based on the local environment including changes upon binding to effectors.